The prevalence of thrombocytopenia in pregnant women in Baghdad: single centre study - Muhammad, Eaman M.; Sabri, Ekhlass H.; Saeed, Hussam D. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: The prevalence of thrombocytopenia in most studies ranges from 7 to 10% of all pregnant females. Although pregnancy is associated with physiological changes that may affect platelet count, several pathological conditions can cause thrombocytopenia which have a significant impact on both the mother and her baby. Objective: The aim of this study was to determine the prevalence of thrombocytopenia in pregnant women attending an out-patient clinic in Al-Yarmouk Teaching hospital in Baghdad. Material and Methods: A cross sectional study conducted at Al-Yarmouk Teaching Hospital from 1st October 2016 to 1st July 2017. Five hundred sixty pregnant women randomly selected as the study group and another 100 non-pregnant women as the control group were enrolled in this study. A complete blood count and blood film were done for both the selected groups. Results: Thrombocytopenia was found in 7.1% of the cases. The most common cause of thrombocytopenia was gestational thrombocytopenia seen in 19(47.5%) patients and PE & HELLP syndrome 9 (22.5%) patients. Most of our cases were asymptomatic and only one case developed heavy vaginal bleeding while there were 2 cases who had platelets below 50,000 considered as severe thrombocytopenia without significant bleeding. Conclusion: Thrombocytopenia is not a rare condition in pregnancy. Accurate etiological diagnosis is essential for effective management. Most of the cases are mild, self-limiting and rarely cause with complications